An analysis on the influence of demand for and supply of funds on the base lending rate / Azman Mohd Zain - Mohd Zain, Azman (1994)
This research analyse the relationship between BLR and the demand for and supply of funds and the economic indicator and to determine the factors that significantly effect the BLR of the commercial banks. Four variables was identified for the analysis, they are the Base Lending Rate (the dependent variable) and Total Deposit (which consists of Demand, Saving and Fixed Deposit), Loan and Advances and Gross Domestic Product represent the independent variable. Data collected for the analysis is from 1987 to 1993.